610 Virtual Burns Care in The Era Of COVID-19: A Regional Burns Unit's Experience. (4th May 2021) - Hayes, J; Clements, J; McGarry, K; Rashid, A
Abstract: Introduction: In response to the COVID-19 pandemic a virtual burns service was established in Northern Ireland to reduce face-to-face consultations to only complex burns or those necessitating hospital admission to the regional unit. Method: A combination of telephone calls, emails, photography, and Microsoft Teams software was utilised to facilitate a virtual review service. Our initial adoption of the system was audited during April and May 2020. Through Plan-Do-Study-Act (PDSA) methodology an electronic tertiary-referral proforma was established prior to closure of the audit cycle in July 2020. Results: From the start of lockdown a significant reduction in face-to-face consultations was observed. Given the increasing use of virtual telephone consultation only 19.5% of the unit's total referrals (April, May, and July) were either reviewed face-to-face in dressing clinic or admitted. A target of 100% data point entry (including demographic, clinical, and initial management) for patients entering the virtual service was set. Following implementation of the e-Referral pathway an improvement in both the detail and completeness (95%) of patient referral information was achieved. Conclusions: Our experience demonstrates that virtual burns care can be safely and rapidly adapted in response to evolving need. The potential role of virtual care post-COVID, in selected patients, is an exciting one.